The Influence of Entrepreneurs’ Psychological Capital on Their Deviant Innovation Behavior - Xu, Wenhai; Zhao, Shouzheng (Frontiers in Psychology, 2020)
This study explores the influence of psychological capital on the deviant innovation behavior, with the purpose of realizing the application and development of positive psychology in the field of innovation and creation. First, the data was obtained based on the questionnaire, and the Likert scale was adopted to measure the variables effectively, in which 1 point means “never,” 2 points mean “rarely,” and 5 points mean “always.” Second, the SPSS 26.0 statistical analysis software was adopted, and a statistical analysis was made on the correlation among deviant innovation, psychological capital, work values, and work remodeling. Third, the relationship between psychological capital and deviant innovation behavior was explored using the analytic hierarchy process (AHP). The results showed that the reliability of each scale is good, Cronbach’s α coefficients are all higher than 0.8, and the fitting effect of the four-factor model is the best, proving that the highest differentiation validity can be achieved using the proposed method. Furthermore, there are significant correlations among entrepreneur’s psychological capital, entrepreneur’s work values, and entrepreneurship work remodeling and deviant innovation behavior, among which the psychological capital and work values are the most correlated with deviant innovation. With the psychological capital of entrepreneurs as the adjustment variable and the interaction added, the explanation rate of the level equation is increased from 17 to 24.2%. Therefore, the psychological capital of entrepreneurs plays a very big role in regulating work values and deviant innovation behavior. In the current environment of innovation and entrepreneurship development, it is necessary for entrepreneurs to give full reign to the regulatory role of their own psychological capital, so as to promote the development of self-active deviant innovation activities and encourage employees to actively innovate and create.